A randomised clinical trial of feedback on inhaler adherence and technique in patients with severe uncontrolled asthma. Issue 1 (4th January 2018) - Sulaiman, Imran; Greene, Garrett; MacHale, Elaine; Seheult, Jansen; Mokoka, Matshediso; D'Arcy, Shona; Taylor, Terence; Murphy, Desmond M.; Hunt, Eoin; Lane, Stephen J.; Diette, Gregory B.; FitzGerald, J. Mark; et al.
In severe asthma, poor control could reflect issues of medication adherence or inhaler technique, or that the condition is refractory. This study aimed to determine if an intervention with (bio)feedback on the features of inhaler use would identify refractory asthma and enhance inhaler technique and adherence. Patients with severe uncontrolled asthma were subjected to a stratified-by-site random block design. The intensive education group received repeated training in inhaler use, adherence and disease management. The intervention group received the same intervention, enhanced by (bio)feedback-guided training. The primary outcome was rate of actual inhaler adherence. Secondary outcomes included a pre-defined assessment of clinical outcome. Outcome assessors were blinded to group allocation. Data were analysed on an intention-to-treat and per-protocol basis. The mean rate of adherence during the third month in the (bio)feedback group (n=111) was higher than that in the enhanced education group (intention-to-treat, n=107; 73% versus 63%; 95% CI 2.8%–17.6%; p=0.02). By the end of the study, asthma was either stable or improved in 54 patients (38%); uncontrolled, but poorly adherent in 52 (35%); and uncontrolled, but adherent in 40 (27%). Repeated feedback significantly improved inhaler adherence. After a programme of adherence and inhaler technique assessment, only 40 patients (27%) were refractory and adherent, and might therefore need add-on therapy. On a period of monitored adherence only 27% of patients were refractory and adherent and thus need add-on therapy http://ow.ly/ddQr30gTpmb